The Appropriate Technology for Aquaponics in Narrow Land by KKN UNS Group in Ngarap-Arap Village, Grobogan - Aziza Ridha Septika; Willis Safitri; Arnold Mario Luhut Martua Tambunan; Mohamad Ashraf Irfanda; Eka Febryani Raihan Putri; Hanifah Pammula Istigfarin; Filia Ariska Meylana; Zuhri, Moh Sayful; Sahirul Alim Tri Bawono (PELITA NUSA TENGGARA, 2022)
Utilization of narrow land is a trend that needs to be developed at this time in supporting family food self-sufficiency. The role and use of yard land varies greatly from one area to another, depending on the level of need, socio-cultural, community education, as well as physical and ecological factors of the local area. Agriculture with aquaponics techniques can provide many benefits to farmers and the community, including being able to produce two products at once, namely fresh organic vegetables and fish. Real Work Lectures (KKN) by Sebelas Maret University students, carry out programs that have been agreed upon and adapted to the needs of the community at the KKN location. The activity was carried out at the home of the head of the Brenggolo hamlet with the work program of Extension on the Utilization of Vertical Farming and Workshop on Appropriate Aquaponic Technology in Narrow Land. Through this program, he hopes to be able to give the role of independence to the community in the use of narrow land in the yard of the house.